(3Mb GdeJge ai GdeMGceI GeGe bGVjg GdWHjYi (B: s (3OQGSI ebGQfI (B/ s - (3Sdje eMeO Sdje MSjf s; (3eCehf eMeO SdGeI (B: s ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI ,s, 2009)
(3jJUOi gPG GdHMK HGdOQGSI hGdJMdjd dKdGKI LhGfH QFjSjI jKjQgG ehVhY Mb GdeJge ai GdeMGceI CeGe bGVjg GdWHjYi Chd gPg GdLhGfH jJYdb HeVehf gPG GdMb heGEPG cGf GdbGfhf gh GdPi jMOOg Ch jfU Ydjg Ce Cf KeI ebheGJ hVeGfGJ jJYjf Cf JJhGaQ ajg aVdG Yf GdfU Ydjg bGfhfG hKGfi gPg GdLhGfH jJYdb HGdeaJQVGJ GdJi jTjO YdjgG gPG GdMb hGdVeGfGJ GdJi jcadgG def jMGce CeGeg hGdJi JejRg hJLYdg GdCcKQ VeGfG ddeJge s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2009s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdbGVi GdWHjYis; (3GdeMGce GdESJKfGFjIs; (3GdeMGce GdeJNUUIs; (3QSGFd LGeYjIs